2018
DOI: 10.1098/rspa.2018.0285
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian adaptation of chaos representations using variational inference and sampling on geodesics

Abstract: A novel approach is presented for constructing polynomial chaos representations of scalar quantities of interest (QoI) that extends previously developed methods for adaptation in Homogeneous Chaos spaces. In this work, we develop a Bayesian formulation of the problem that characterizes the posterior distributions of the series coefficients and the adaptation rotation matrix acting on the Gaussian input variables. The adaptation matrix is thus construed as a new parameter of the map from input to QoI, estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…which is estimated using the n MC realizations {[𝜼 i,𝓁 ar ], 𝓁 = 1, … , n MC }. Equation ( 7) contains the information defined by Equation (8). Indeed it is easy to verify that we have the relation…”
Section: Learned Data Set Generated By With-group Plommentioning
confidence: 84%
See 2 more Smart Citations
“…which is estimated using the n MC realizations {[𝜼 i,𝓁 ar ], 𝓁 = 1, … , n MC }. Equation ( 7) contains the information defined by Equation (8). Indeed it is easy to verify that we have the relation…”
Section: Learned Data Set Generated By With-group Plommentioning
confidence: 84%
“…The probabilistic learning on manifolds (PLoM) method was proposed in 2016 1 as a complementary approach to existing methods in machine learning for sampling underlying distributions on manifolds. [2][3][4][5][6][7][8][9] It allows for solving unsupervised and supervised problems under uncertainty for which the training sets are small. This situation is encountered in many problems of physics and engineering sciences with expensive function evaluations.…”
Section: About the Plommentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, techniques for sampling from distributions defined on Stiefel manifolds as in [9] would enable estimation of posterior distributions of projection matrices and would be another step towards the ultimate goal that is the fully Bayesian solution of the problem. Recent progress on this direction has shown that an approach for sampling from the marginal posteriors of the coefficients and the rotation matrix, using a combination of variational inference and hamiltonian Monte Carlo on the Stiefel manifold, can result in an efficient way of exploring the joint posterior [55], though more generic approaches are yet to be developed. Here we seek to derive the gradient of the 2 error function…”
Section: Discussionmentioning
confidence: 99%
“…The use of the PCE for constructing a parameterized representation of a non-Gaussian random field that models the parameter of a boundary value problem, in order to identify it solving a statistical inverse problem has been initiated in [13,18,14] and used and revisited in [11,23,10,42,35,36,8,34,45] for statistical inverse problems in low or in high stochastic dimension. For the statistical inverse identification of the coefficients of the PCE, the Bayesian approach has been proposed in [18,32,2,43,38,29,50,41,56].…”
mentioning
confidence: 99%